2010
DOI: 10.1373/clinchem.2010.144709
|View full text |Cite
|
Sign up to set email alerts
|

The Silencing of MicroRNA 148a Production by DNA Hypermethylation Is an Early Event in Pancreatic Carcinogenesis

Abstract: BACKGROUND:The poor prognosis of pancreatic ductal adenocarcinoma (PDAC) is accounted for by the absence of early diagnostic markers and effective treatments. MicroRNAs inhibit the translation of their target mRNAs. The production of microRNAs is strongly altered in cancers, but the causes of these alterations are only partially known. DNA hypermethylation is a major cause of gene inactivation in cancer. Our aims were to identify microRNAs whose gene expression is inactivated by hypermethylation in PDAC and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
108
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(115 citation statements)
references
References 32 publications
5
108
1
Order By: Relevance
“…6 Hanoun et al have reported that hypermethylation of the promoter region encoding miR-148a is responsible for its repression not only in PDAC samples but also in preneoplastic-pancreatic-intraepithelial-neoplasia (PanIN) and can serve as an ancillary marker for the differential diagnosis of PDAC and chronic pancreatitis. 21 Consistent with this observation, we report that miR-148a is significantly down-regulated in micro-dissected PDAC samples. Therefore the expression of miR-148a in TGFb non-responsive IMIM-PC2 pancreatic cancer cells is probably regulated by DNA-methylation.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…6 Hanoun et al have reported that hypermethylation of the promoter region encoding miR-148a is responsible for its repression not only in PDAC samples but also in preneoplastic-pancreatic-intraepithelial-neoplasia (PanIN) and can serve as an ancillary marker for the differential diagnosis of PDAC and chronic pancreatitis. 21 Consistent with this observation, we report that miR-148a is significantly down-regulated in micro-dissected PDAC samples. Therefore the expression of miR-148a in TGFb non-responsive IMIM-PC2 pancreatic cancer cells is probably regulated by DNA-methylation.…”
Section: Discussionsupporting
confidence: 85%
“…6,21,27 In colon, lung, breast, and head and neck carcinoma and melanoma, miR-148a-promoter hypermethylation has been correlated with a higher metastatic potential. 6 Hanoun et al have reported that hypermethylation of the promoter region encoding miR-148a is responsible for its repression not only in PDAC samples but also in preneoplastic-pancreatic-intraepithelial-neoplasia (PanIN) and can serve as an ancillary marker for the differential diagnosis of PDAC and chronic pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Down-regulation of miR-148a is an early marker of pancreatic adenocarcinoma and is already decreased in pre-neoplastic PanIN lesions. 42 At least 27 target genes are known for miR-148a, including bladder cancer associated protein. 43 In our study, miR-148a expression is related to KRAS mutations in pancreatic and ampullary adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that miRNA profiles can also differentiate between benign and malignant cystic lesions [14][15][16][17][18][19]. In addition, a few small studies have shown that the detection of miRNAs in FNA samples taken at EUS is feasible and may increase the sensitivity and specificity of detecting malignant change in cystic lesions of the pancreas [17,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%